2012
DOI: 10.2136/sssaj2012.0096
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effects of Mineral and Organic Fertilizer on Denitrifiers, Nitrous Oxide Emissions and Denitrification in Long‐Term Amended Vineyard Soils

Abstract: Short‐term effects (i.e., 21 d) of mineral or organic fertilizer application on long‐term (i.e., 8 yr of applications) amended soil on denitrifier community abundance, denitrification gene mRNA transcript numbers, denitrification rate, and emissions of N2O were explored. Soil was collected from a vineyard in Italy receiving annual applications of either mineral fertilizer (conventional management system, CS) or municipal compost (organic management system, OS). Each soil was incubated using three treatments: n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 47 publications
3
14
1
Order By: Relevance
“…In contrast, N fertilization seemed to have a negative influence on the richness and diversity of active nosZ bacterial community and supported the hypothesis that fertilizer management could affect the N 2 O:N 2 emission ratio from denitrification and consequently the potential activity of bacteria involved in the last step of denitrification process (Philippot et al, 2007). Moderate to important modifications in the structure of the denitrifying community in response to fertilizer addition have been reported depending on the type of fertilizer and also on the time scale of the field experiment (Philippot et al, 2007;Chèneby et al, 2009;Tatti et al, 2012).…”
Section: Diversity Of Soil Denitrifying Communitiessupporting
confidence: 63%
“…In contrast, N fertilization seemed to have a negative influence on the richness and diversity of active nosZ bacterial community and supported the hypothesis that fertilizer management could affect the N 2 O:N 2 emission ratio from denitrification and consequently the potential activity of bacteria involved in the last step of denitrification process (Philippot et al, 2007). Moderate to important modifications in the structure of the denitrifying community in response to fertilizer addition have been reported depending on the type of fertilizer and also on the time scale of the field experiment (Philippot et al, 2007;Chèneby et al, 2009;Tatti et al, 2012).…”
Section: Diversity Of Soil Denitrifying Communitiessupporting
confidence: 63%
“…To a lesser extent nir richness, diversity and abundance correlated with other measures of soil fertility such as increase in pH, soluble C, and NH 4 + contents, these findings agree with previous studies that have found the composition of soil denitrifier communities to be sensitive to a variety of soil chemical characteristics (Jones and Hallin, 2010;Reyna et al, 2010;Chon et al, 2011;Miller et al, 2008;Tatti et al, 2013).…”
Section: Influence Of Soil Characteristics On Denitrifier Gene Richnesupporting
confidence: 91%
“…E-N relationships corresponding to the subfunctions of EFs are illustrated in Figure 2 for upland grain crops and paddy rice under positive or negative ΔEFs. The diagnostic of negative ΔEFs (Figures 2b and 2d) suggests that activity or efficiency of nitrifier and denitrifier communities may reach thresholds and further stabilize around these thresholds, when N inputs exceed crop requirements [Ju et al, 2009;Tatti et al, 2013]. However, the strange decrease in E (as the green line in Figure 2b and ΔEF = À0.0037% · kg À1 N 2 O-N · ha) does not have a satisfactory theoretical explanation, though this type of trend was occasionally observed [van Groenigen et al, 2004;Hoogendoorn et al, 2008;Iqbal, 2009;Wang et al, 2011a;Zhang et al, 2012;Signor et al, 2013;Zhou et al, 2013].…”
Section: 1002/2014gb005046mentioning
confidence: 99%